Towards the elimination of Plasmodium vivax malaria: Implementing the radical cure. - Kamala Thriemer; Benedikt Ley; Lorenz von Seidlein (PLoS Medicine, 2021)
In this review for the Vivax malaria collection, Kamala Thriemer and colleagues explore efforts to eliminate P. vivax malaria.